Postnatal Epigenetic Alterations in Calves Persistently Infected with Bovine Viral Diarrhea Virus - Jessica N. Kincade; Dilyara A. Murtazina; Hanah M. Georges; Carolina L. Gonzalez-Berrios; Jeanette V. Bishop; Terry E. Engle; Marcela Henao-Tamayo; Jordan M. Eder; Erin M. McDonald; Darcy M. Deines; Brie M. Wright; Hana Van Campen; et al. (Viruses)
Bovine viral diarrhea virus (BVDV) is a globally prevalent pathogen causing severe detriment to the cattle industry. Vertical infection occurring before the development of the fetal adaptive immune response, before 125 days of gestation, results in an immunotolerant, persistently infected (PI) calf. It was hypothesized that epigenetic alterations observed in the splenic tissue of PI fetuses at gestational day 245 would persist into the postnatal period. White blood cell DNA from five PI and five control heifers at 4 months of age was subjected to reduced representation bisulfite sequencing and interpreted within the context of complete blood count and flow cytometry data herein. Analysis revealed 8367 differentially methylated sites contained within genes associated with the immune and cardiac system, as well as hematopoiesis. Differences observed in the complete blood counts of PI heifers include increased monocytes, microcytic anemia, and elevated platelets with decreased mean platelet volume. Flow cytometry revealed increased classical monocytes, B cells, and CD4+/CD8B+ and CD25+/CD127− T cells, as well as decreased γδ+, CD4+, and CD4−/CD8B− T cells. Investigation of the PI methylome provides a new perspective on the mechanisms of pathologies and provides potential biomarkers for the rapid identification of PI cattle.